Atrial Fibrillation Ablation Using Robotic Magnetic Navigation Reduces the Incidence of Silent Cerebral Embolism - Zheng, Jie; Wang, Meng; Tang, Qun-feng; Xue, Feng; Li, Ku-lin; Dang, Shi-peng; Liu, Xiao-yu; Zhao, Xiao-xi; Zhang, Chang-ying; Yu, Zhi-ming; Han, Bing; Jiang, Ting-bo; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The incidence of silent cerebral embolisms (SCEs) has been documented after pulmonary vein isolation using different ablation technologies; however, it is unreported in patients undergoing with atrial fibrillation (AF) ablation using Robotic Magnetic Navigation (RMN). The purpose of this prospective study was to investigate the incidence, risk predictors and probable mechanisms of SCEs in patients with AF ablation and the potential impact of RMN on SCE rates. Methods and Results: We performed a prospective study of 166 patients with paroxysmal or persistent AF who underwent pulmonary vein isolation. Patients were divided into RMN group (n = 104) and manual control (MC) group (n = 62), and analyzed for their demographic, medical, echocardiographic, and risk predictors of SCEs. All patients underwent cerebral magnetic resonance imaging within 48 h before and after the ablation procedure to assess cerebral embolism. The incidence and potential risk factors of SCEs were compared between the two groups. There were 26 total cases of SCEs in this study, including 6 cases in the RMN group and 20 cases in the MC group. The incidences of SCEs in the RMN group and the MC group were 5.77 and 32.26%, respectively (X2 = 20.63 P < 0.05). Univariate logistic regression analysis demonstrated that ablation technology, CHA2DS2-VASc score, history of cerebrovascular accident/transient ischemic attack, and low ejection fraction were significantly associated with SCEs, and multivariate logistic regression analysis showed that MC ablation was the only independent risk factor of SCEs after an AF ablation procedure. Conclusions: Ablation technology, CHA2DS2-VASc score, history of cerebrovascular accident/transient ischemic attack, and low ejection fraction are associated with SCEs. However, ablation technology is the only independent risk factor of SCEs and RMN can significantly reduce the incidence of SCEs resulting from AF ablation. Clinical Trial Registration: ChiCTR2100046505.